2012
DOI: 10.14419/ijbas.v2i1.642
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of geothermal gradient and heat flow distribution in Delta State, Nigeria

Abstract: Geothermal and heat flow distribution study was carried out at eighteen locations in Delta State, Nigeria using data obtained from temperature logging and thermal conductivity measurements. The result from the study showed that the geothermal gradients of the area ranged between 25.47 and 31.16 °C/km while the mean geothermal gradient was obtained as 28.64 °C/km. This finding revealed that the geothermal gradient of the area lies within the range interval commonly encountered in tectonically inactive regions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Noise on the weekend is less than on weekdays, and noise in the day is less than at night [44]. Noise can significantly impact health, for example, headaches, stress, and increased blood pressure [45,46]. The study results indicated that the noise level in the study area is within the limit of QCVN 26:2010/BTNMT (70 dBA).…”
Section: Air Quality In the Study Areamentioning
confidence: 79%
“…Noise on the weekend is less than on weekdays, and noise in the day is less than at night [44]. Noise can significantly impact health, for example, headaches, stress, and increased blood pressure [45,46]. The study results indicated that the noise level in the study area is within the limit of QCVN 26:2010/BTNMT (70 dBA).…”
Section: Air Quality In the Study Areamentioning
confidence: 79%
“…As sand percentages de crease eastwards and seawards, thermal gradient increases. A number of thermograms here have a concaved shape to depth axis [48]. It was reported that the movement of fluids in the Niger Delta influence the thermal field pattern and heat flow distribution within the Basin.…”
Section: E N D I N G T a B L Ementioning
confidence: 79%
“…Geothermal observations in the southern part of Nigeria (Niger Delta and Anambra Basin) were studied by [31; 39-42]. Studies of geothermal field in this structure were actively conducted recently [43][44][45][46][47][48][49]. Results of heat flow studies in the Niger Delta were also published [50 -52].…”
Section: E N D I N G T a B L Ementioning
confidence: 99%
“…A resistivity method is a technique most commonly used for hydrogeological investigations. Groundwater investigations have been carried out using the resistivity method [4], [5], [6], [7], [8], [9], [10], [11], [12]. The resistivity method is used because of its ease of measurement in the field, and the ability to produce information about depths ranging from a few meters to hundreds of meters.…”
Section: Figure 1 Schematic Cross-sectional Illustrating Aquifer [3]mentioning
confidence: 99%